Clinical Presentation and the Outcome of Management of Neonatal Abdominal Wall Defects at Gezira National Centre for Pediatric Surgery, March 2008 to February 2013 - Adam, Adam M I; Nugud, Faial A; Osman, Osman T M (Gezira Journal of Health Sciences, 2014)
Objective: Anterior abdominal wall defects represent unique challenges to pediatric surgeons and offer insight into normal fetal development. Our main goal is to study the ation and the outcome of management of abdominal wall defects in neonates managed at Gezira National Centre of Pediatric Surgery. Patients andMethods: This is a retrospective, prospective, descriptive hospital based study of patients presenting with clinical aspects of abdominal wall defects who were admitted to hospital in Gezira National Center of Pediatric Surgery (GNCPS) in Gezira state, Sudan, over 5years between March 2008 and Feb. 2013. Results: The common age group is neonates, and most cases presented earlier than 24 hours (64.1%). Regarding the presenting symptoms, (33.3%) presented with eviscerated the small intestine was the most commonly eviscerated in (17.5%), and the liver was eviscerated in (4.8%). The operative mortality was 30 %. T he analysis of the type of found that: 13 patients (20.6%) were delivered vaginally at hospital, 10 patients (15.9%) were delivered by C/S, and 40 patients (63.5%) were delivered vaginally According to the management, surgery was done to 30 cases (47.6%), non surgical treatment done for 33 cases (52.4%) with good outcome. Primary closure was done for 20 cases (66.7%), Blood bank bag operation underwent for 6 cases (20.0%), and delayed hernia defects repair was done for 4 cases (13.3%). The trend in the centre is to conserve patients with intact membrane. Those with ruptured omphalocele, gastroschisis bowl obstruction will undergo urgent surgery. The analysis of the which revealed:  Mortality of 9 cases (30%) the majority was due to failure and sepsis. Six cases had late complications (20%) were ventral hernia, and 27 cases had early complications (50%) most of these were The overall mortality (30 %) can be explained by the lack of neonatal intensive care unit and unavailability of long term total parenteral nutrition. In Lukman study the mortality rate was 30.4% which is similar to ours (13). The overall survival in children with omphalocele and gastroschisis is now reduced to less than 10 % in developed countries especially in isolated cases without chromosomal anomalies or major organ malformation(17). Conclusion: The management of the anterior abdominal wall defect is challenging and need urgent intervention. Early presentation improves the management out come and decreases the mortality and complications, this need proper antenatal care follow up.